Case Report: A novel variant of the TTN gene and two other rare variants in a Chinese patient with dilated cardiomyopathy - Shan Han; Ying-Yi Zhang; Jie Geng (Frontiers in Cardiovascular Medicine)
Genetic factors are estimated to cause approximately 30%–50% of dilated cardiomyopathy (DCM) cases, with Titin (TTN) being the most commonly implicated gene, accounting for 20%–25% of genetic causes. Many DCM-causing TTN mutations are heterozygous truncating variants, including frameshift, non-sense, and essential splice site mutations. SCN5A mutations are associated with arrhythmias, while pathogenic variants in the low-density lipoprotein receptor (LDLR) gene are associated with familial hypercholesterolemia. Here, we report a case of DCM with a novel TTN variant, as well as two rare variants in the SCN5A and LDLR genes. It is rare for a patient to have three rare genetic variations and this may expand the genetic map of DCM and TTN, offering important insights for future studies on their genetic and disease relationships.